A high entropy polyanion type positive electrode material modified by anion and cation functionalization doping, preparation method and application thereof
By introducing various functional anion and cation groups into the positive electrode material of sodium ion battery, a high entropy structure is constructed, and the problems of low electronic conductivity and insufficient discharge capacity of existing materials are solved, and high discharge capacity and stability are improved. In the large-scale application of sodium ion batteries.
Patent Information
- Application Number
- CN202211167558.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-23
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-09-23
AI Technical Summary
The existing sodium ion battery cathode materials have shortcomings in terms of cost, performance and cycle stability, especially the problems of low electronic conductivity and low discharge capacity, which limits their large-scale application.
Using anionic and cationic functional doping modified high-entropy polyanionic cathode material, the material structure stability, working voltage and electron conductance are directionally regulated by introducing multiple functional anionic and cationic groups, and local chemical bonds and electron distribution are adjusted to build a high-level Entropy structure to improve sodium storage performance.
It achieves high discharge capacity, capacity retention rate up to 98%, operating voltage improvement and conductivity optimization, reducing material costs while improving cycle stability and rate performance.
Smart Images

Figure CN115360340B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-entropy polyanion-type positive electrode material modified by anion and cation functionalization doping, a preparation method and application thereof, and belongs to the technical field of sodium ion batteries. Background Art
[0002] As fossil energy is depleted, the energy crisis becomes increasingly prominent, and the development of clean and renewable energy is imminent. In the process of integrating new energy sources, large-scale energy storage technology is needed to achieve efficient utilization and interconnection of clean energy. In this context, sodium-ion batteries, which have similar working principles to lithium batteries, have shown high research value and application prospects in the field of secondary energy storage due to their multiple advantages such as abundant resources, wide distribution, low price, and high safety. Compared with lithium ions, sodium ions have a large radius and heavy mass, and the targeted development of positive electrode materials is the key to improving the comprehensive performance of sodium-ion batteries.
[0003] Among the reported positive electrode materials, polyanionic phosphates have become the most popular active materials for the development of high-power sodium-ion batteries due to their high operating voltage and excellent structural stability. This type of material has a highly open skeleton structure, which provides abundant diffusion channels for the migration of sodium ions. Its performance is comparable to that of lithium iron phosphate in lithium-ion batteries, especially vanadium-based phosphates. However, due to the high cost and certain toxicity of vanadium-based raw materials, the unique cost advantage of sodium-ion batteries is weakened. In addition, this type of positive electrode has poor intrinsic conductivity, resulting in shortcomings in both performance and cost of the material, which greatly limits its large-scale application. In recent years, Ti 3+ / Ti 4+ , Fe 2+ / Fe 3+ , Mn 2+ / Mn 3+ 、Ni 2+ / Ni 3+ The redox couple has been reported in a variety of NASICON compounds, such as Na3VTi(PO4)3, Na4VFe(PO4)3, Na4MnV(PO4)3, Na 3+ x V x Ni 1-x (PO4)3, etc. Compared with pure vanadium phosphate positive electrode, these new component materials effectively reduce the cost of raw materials, but the modified materials are often difficult to maintain the original capacity and voltage advantages. To address the defect of low electronic conductivity of materials, the commonly used strategy is carbon coating in various forms and methods. Although carbon coating can effectively improve the conductivity of materials, and is low-cost and easy to operate, the difference in compatibility between the carbon layer and the bulk structure and the limitation of carbon content on ion migration will greatly reduce the coating effect.
[0004] CN202110812852.0 discloses a modified sodium manganese titanium phosphate positive electrode material, which uses a cost-effective transition metal element to replace vanadium, and uses a stronger electronegative anion to replace part of the phosphate, adjusts the bond length and binding energy of the metal-oxygen bond, and gives full play to the two platform capacities of the manganese element. At the same time, it changes the electronic configuration and covalent bond characteristics of the polyanion framework structure, showing a relatively excellent sodium storage performance, but its first-week coulomb efficiency is low and the discharge capacity is low.
[0005] Chinese patent application 202111458385.2 discloses a manganese-based polyanion sodium ion battery positive electrode material using SiO4 4- Replace part of PO4 3- , and the obtained positive electrode material presents a hollow sphere with a hollow interior, which effectively improves the problems of poor electrochemical activity and low electronic conductivity of manganese-based phosphate. In addition, the regular morphology makes the material have good dispersibility, alleviates the agglomeration phenomenon between particles, and is conducive to the efficient transmission of sodium ions in the solid phase. However, the cycle stability and rate performance of this material still have a lot of room for improvement.
[0006] Chinese patent application 202210024348.9 discloses a polyanionic sodium-ion battery positive electrode material and a preparation method thereof. By introducing a variety of cheap inactive metals to stabilize the material structure, the cycle performance and rate performance of the material are effectively improved. However, since the inactive elements occupy the crystal structure position but do not play an electrochemical role, the discharge capacity of the material is still low even when charged to a higher voltage. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a high-entropy polyanion-type cathode material modified by anion and cation functionalization doping, a preparation method and its application. By introducing a variety of functional anion and cation groups, the structural stability, working voltage and electronic conductivity of the material are directional controlled, the local chemical bonds and electron distribution are adjusted, and precise lattice control is achieved to improve the sodium storage performance of the material.
[0008] To achieve the above object, the technical solution of the present invention is as follows:
[0009] A high entropy polyanion positive electrode material modified by anion and cation functionalization doping, the positive electrode material comprises a positive electrode core and a carbon coating layer, the chemical formula of the positive electrode core is Na δ A α B β C γ X σ Y m Z n , where A is V 3+ and / or Fe 2+ , B is Cu 2 +, Mn 2+ and Cr 3+ One or more of the following, C is Ni 2+ and / or Ti 4+ , X is PO4 3- and / or P2O7 4- , Y is SO4 2- 、N 3- and F - More than one of the following, Z is BO3 3- 、SiO4 4- , S 2- and Cl - At least one of the following, 1.2≤δ≤4.8, 0.7≤α≤1.4, 0.16≤β≤0.75, 0.3≤γ≤0.8, 2.1≤σ≤2.8, 0.15≤m≤0.75, 0.15≤n≤0.6; the particle size of the high entropy polyanion positive electrode material is 10μm~40μm, and the thickness of the carbon coating layer is 5nm~10nm.
[0010] Preferably, 2≤δ≤3.5, 0.8≤α≤1.2, 0.3≤β≤0.6, 0.4≤γ≤0.6, 2.2≤σ≤2.6, 0.2≤m≤0.5, and 0.2≤n≤0.4.
[0011] Preferably, the chemical formula of the positive electrode core is Na 2.6 VFe 0.2 Mn 0.3 Ti 0.5 (PO4) 2.2 (SO4) 0.4 (BO3) 0.4 、Na3VMn 0.5 Ti 0.5 (PO4) 2.4 (SO4) 0.3 (BO3) 0.3 、Na 3.1 V 0.8 Fe 0.4 Mn 0.4 Ti 0.4 (PO4) 2.4 (SO4) 0.3 (BO3) 0.3 、Na 2.4 V 0.6 Ti 0.4 (PO4) 2.6 (SO4) 0.2 (BO3) 0.2 、Na 3.5 Fe 0.9 Mn 0.6 Ti 0.5 (PO4)2.2 (SO4) 0.5 (BO3) 0.3 Or Na 3.3 VFe 0.2 Cu 0.3 Ti 0.5 (PO4) 2.2 (SO4) 0.4 (BO3) 0.4 .
[0012] A method for preparing the high entropy polyanion positive electrode material modified by anion and cation functionalization doping according to the present invention, the method steps comprising:
[0013] (1) adding a sodium source, a transition metal A source, a transition metal B source, a transition metal C source, a polyanion X source, a polyanion Y source, a polyanion Z source and a carbon source into a volatile solvent, heating and stirring until the solvent is evaporated to dryness, thereby obtaining a precursor;
[0014] (2) sintering the precursor in a protective gas atmosphere to obtain a high-entropy polyanion positive electrode material modified by anion and cation functionalization doping;
[0015] Wherein, in step (1), the molar ratio of the sodium source to the total amount of the transition metal source is 0.6-2.4:1, the molar ratio of the sodium source to the total amount of the polyanion source is 0.4-1.6:1, and the molar ratio of the carbon source to the total amount of the transition metal source is 1-6:1;
[0016] In step (2), the sintering temperature is 300° C. to 800° C., and the sintering time is 4 h to 20 h.
[0017] Preferably, in step (1), the molar ratio of the sodium source to the total amount of the transition metal source is 1 to 2:1, the molar ratio of the sodium source to the total amount of the polyanion source is 0.8 to 1.2:1, and the molar ratio of the carbon source to the total amount of the transition metal source is 3 to 6:1.
[0018] Preferably, in step (1), the sodium source includes one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium formate, sodium acetate and sodium nitrate.
[0019] Preferably, in step (1), in the source of transition metal A, the vanadium source is one or more of vanadium trichloride, vanadium tribromide, vanadium trioxide, vanadium acetylacetonate, vanadium oxychloride, vanadium oxysulfate, vanadium oxyoxalate, vanadium dioxide, vanadium acetylacetonate, vanadium oxychloride, sodium vanadate, sodium metavanadate, ammonium metavanadate, vanadium pentoxide and metallurgical vanadium slag; the iron source is one or more of ferrous fluoride, ferrous chloride, ferrous bromide, ferrous nitrate, ferrous sulfate, ferrous carbonate, ferrous oxalate, ferrous acetate, ferrous hydroxide, ferrous oxide, ferrous sulfide, ferrous acetylacetonate, ferrous trifluoride, ferric chloride, ferric bromide, ferric nitrate, ferric sulfate, ferric carbonate, ferrous oxalate, ferric acetate, ferric hydroxide, ferrous oxide, ferrous oxide and ferrous acetylacetonate.
[0020] In the transition metal B source, the copper source is one or more of copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide and copper acetylacetonate; the manganese source is one or more of manganous fluoride, manganous chloride, manganous bromide, manganous nitrate, manganous sulfate, manganous carbonate, manganous oxalate, manganous acetate, manganous hydroxide, manganous oxide, manganous sulfide, manganous acetylacetonate, manganous trifluoride, manganous trichloride, manganous tribromide, manganous nitrate, manganous sulfate, manganous carbonate, manganous oxalate, manganous acetate, manganous hydroxide, manganous trioxide, manganous dioxide and manganous acetylacetonate; the chromium source includes one or more of chromium trichloride, chromium tribromide, chromium nitrate, chromium sulfate, chromium oxalate, chromium formate, chromium acetate, chromium chromate, chromium lactate, basic chromium sulfate, chromium perchlorate, chromium trioxide, chromium hydroxide, chromium acetylacetonate, sodium chromate and sodium dichromate.
[0021] In the transition metal C source, the nickel source is one or more of nickelous fluoride, nickelous chloride, nickelous bromide, nickelous nitrate, nickelous sulfate, nickelous carbonate, nickelous oxalate, nickelous acetate, nickelous hydroxide, nickelous oxide, nickelous sulfide and nickelous acetylacetonate; the titanium source is one or more of titanium chloride, titanium bromide, titanium sulfate, titanium nitrate, titanium oxalate, titanium formate, titanium acetate, titanium dioxide, titanium acetylacetonate and tetrabutyl titanate;
[0022] When the transition metal exhibits a high valence, a reducing agent is also added.
[0023] Preferably, the reducing agent includes one or more of ascorbic acid, oxalic acid, citric acid, charcoal and hydroxylamine hydrochloride.
[0024] Preferably, in step (1), the polyanion X source is PO4 3- 、P2O7 4- The corresponding acid and / or salt; the polyanion Y source includes SO4 2- 、N 3- 、F - The corresponding acid and / or salt; the polyanion Z source is BO3 3-、SiO4 4- , S 2- , Cl - SO4 2- 、N 3- 、F - The corresponding acids and / or salts.
[0025] Preferably, in step (1), the carbon source includes one or more of citric acid, sodium citrate, sodium oleate, oleic acid, polyvinyl pyrrolidone, glucose, sucrose, starch, dopamine hydrochloride, starch, graphene, Ketjen black and carbon nanotubes.
[0026] Preferably, in step (1), the solvent is one or more of water, ethanol, acetone and ethyl acetate; the heating and stirring temperature is 60°C to 200°C, the stirring speed is 300rpm to 1000rpm, and the time is 1h to 6h.
[0027] Preferably, in step (2), the sintering temperature is 400° C. to 600° C., and the sintering time is 6 h to 12 h.
[0028] Preferably, in step (2), the protective gas is nitrogen or an inert gas.
[0029] A sodium ion battery, wherein the positive electrode material of the battery adopts the high entropy polyanion positive electrode material modified by anion and cation functionalization doping described in the present invention.
[0030] Beneficial Effects
[0031] 1. The present invention provides a high entropy polyanion type positive electrode material modified by anion and cation functionalization doping, and adopts the synergistic effect of anion and cation to carry out directional design of the distribution of transition metal sites and polyanion sites, transition metal A and polyanion X are used to stabilize the structure framework, transition metal B and polyanion Y are used to increase the working voltage, and transition metal C and polyanion Z are used to adjust the structural band gap; through the coordinated design of stabilizing the structural framework, increasing the working voltage and reducing the structural band gap, a high entropy structure compatible with anion and cation is constructed, and the normalized growth and directional construction of the crystal phase are controlled to achieve the coordinated control of cost advantage, voltage capacity advantage and conductivity advantage. Compared with the traditional doping and coating strategy, the design and synthesis of high entropy NASICON materials adopts the scheme of functional group matching, and the introduction of elements not only does not lose its own sodium storage performance, but also can synergistically strengthen its inherent defects; starting from the crystal structure of the material, the intrinsic physical properties and the material crystal phase are regulated, the local electronic structure is changed synchronously, and the intrinsic electronic conductivity is improved.
[0032] 2. The present invention provides a sodium ion battery assembled with the high entropy polyanion positive electrode material modified by anion and cation functionalization doping as the positive electrode material, which has a high discharge capacity and a capacity retention rate of up to 98%. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the XRD spectrum of the high entropy polyanion positive electrode material prepared in Example 1 of the present invention.
[0034] Figure 2 This is the structural model of the high entropy polyanion positive electrode material prepared in Example 2 of the present invention.
[0035] Figure 3 This is a SEM image of the high entropy polyanion positive electrode material prepared in Example 2 of the present invention.
[0036] Figure 4 This is a charge and discharge curve diagram of the high entropy polyanion positive electrode material prepared in Example 3 of the present invention at 0.2C. DETAILED DESCRIPTION
[0037] The present invention will be further described in detail below in conjunction with specific embodiments.
[0038] Example 1
[0039] (1) Sodium nitrate, vanadium acetylacetonate, manganese acetate, tetrabutyl titanate, phosphoric acid, ammonium sulfate, and boric acid in a molar ratio of 2.4:1.0:0.6:0.4:1.5:0.8:0.7 are added to an ethanol solution containing citric acid, and the molar ratio of citric acid to transition metal salt is 1:1; then the mixed solution is placed on a constant temperature heating table at 60°C and magnetically stirred at a speed of 300 rpm. After stirring for 6 hours, the solvent is completely evaporated to obtain a precursor;
[0040] (2) The precursor is placed in a tubular furnace in an argon atmosphere and sintered at 800° C. for 4 hours to obtain a high-entropy polyanion positive electrode material modified by anion and cation functionalization doping.
[0041] The XRD pattern of the positive electrode material is as follows Figure 1 As shown by Figure 1 It can be seen that the diffraction peaks of the cathode material can be assigned to the standard spectrum, and the crystallinity is good, indicating that the obtained high entropy polyanion cathode material is pure phase. The crystal structure of the corresponding components is constructed by first principle, such as Figure 2 As shown, the results show that this design can obtain a stable high-entropy solid solution, and the simulated material shows a lower band gap, verifying the advantages of high-entropy material design.
[0042] Example 2
[0043] (2) Sodium acetate, ferrous acetylacetonate, cupric acetate, nickel nitrate, pyrophosphoric acid, ammonium fluoride, and silicic acid in a molar ratio of 4.6:1.0:0.2:0.8:2.0:0.4:0.6 are added to an aqueous solution containing glucose, and the molar ratio of glucose to transition metal salt is 6:1; the mixed solution is then placed on a constant temperature heating table at 200°C and magnetically stirred at a speed of 1000 rpm. After stirring for 1 hour, the solvent evaporates completely to obtain a precursor;
[0044] (2) The precursor is placed in a tubular furnace in an argon atmosphere and sintered at 400° C. for 10 hours to obtain a high-entropy polyanion positive electrode material modified by anion and cation functionalization doping.
[0045] The XRD test result of the positive electrode material shows that the diffraction peak of the positive electrode material can be assigned to the standard spectrum correspondingly, and the crystallinity is good, indicating that the obtained high entropy polyanion positive electrode material is a pure phase.
[0046] The SEM image of the modified high entropy polyanion cathode material is as follows: Figure 3 As shown by Figure 3 It can be seen that the prepared material presents a block structure of about 20 μm.
[0047] Example 3
[0048] (1) Sodium formate, ammonium metavanadate, ferrous nitrate, manganese acetate, tetrabutyl titanate, phosphoric acid, ammonium sulfate, and boric acid in a molar ratio of 2.6:1.0:0.2:0.3:0.5:2.2:0.4:0.4 are added to an ethanol solution containing polyvinyl pyrrolidone, and the molar ratio of polyvinyl pyrrolidone to transition metal salt is 5:1; then the mixed solution is placed on a constant temperature heating table at 100° C. and magnetically stirred at a speed of 800 rpm. After stirring for 1 hour, the solvent is completely evaporated to obtain a precursor;
[0049] (2) The precursor is placed in a tubular furnace in an argon atmosphere and sintered at 600° C. for 6 hours to obtain a high-entropy polyanion positive electrode material modified by anion and cation functionalization doping.
[0050] The XRD test result of the positive electrode material shows that the diffraction peak of the positive electrode material can be assigned to the standard spectrum correspondingly, and the crystallinity is good, indicating that the obtained high entropy polyanion positive electrode material is a pure phase.
[0051] Comparative Example 1
[0052] (1) Sodium formate, ammonium metavanadate, and phosphoric acid in a molar ratio of 3:2:3 are added to an ethanol solution containing polyvinyl pyrrolidone, and the molar ratio of polyvinyl pyrrolidone to transition metal salt is 1:1; then the mixed solution is placed on a constant temperature heating table at 60°C and magnetically stirred at a speed of 300 rpm. After stirring for 6 hours, the solvent evaporates completely to obtain a precursor;
[0053] (2) The precursor is placed in a tubular furnace in an argon atmosphere and sintered at 800° C. for 4 hours to obtain a high entropy polyanion positive electrode material.
[0054] Comparative Example 2
[0055] (1) Sodium nitrate, vanadium acetylacetonate, tetrabutyl titanate, phosphoric acid, ammonium sulfate, and boric acid in a molar ratio of 1.3:1.0:1.0:1.5:0.8:0.7 are added to an ethanol solution containing citric acid, and the molar ratio of citric acid to transition metal salt is 1:1; the mixed solution is then placed on a constant temperature heating table at 60°C and magnetically stirred at a speed of 300 rpm. After stirring for 6 hours, the solvent evaporates completely to obtain a precursor;
[0056] (2) The precursor is placed in a tubular furnace in an argon atmosphere and sintered at 800° C. for 4 hours to obtain a high entropy polyanion positive electrode material.
[0057] Comparative Example 3
[0058] (1) Sodium nitrate, vanadium acetylacetonate, manganese acetate, tetrabutyl titanate, phosphoric acid, and ammonium sulfate in a molar ratio of 1.7:1.0:0.6:0.4:1.5:1.5 are added to an ethanol solution containing citric acid, and the molar ratio of citric acid to transition metal salt is 1:1; the mixed solution is then placed on a constant temperature heating table at 60°C and magnetically stirred at a speed of 300 rpm. After stirring for 6 hours, the solvent is completely evaporated to obtain a precursor;
[0059] (2) The precursor is placed in a tubular furnace in an argon atmosphere and sintered at 800° C. for 4 hours to obtain a high entropy polyanion positive electrode material.
[0060] Comparative Example 4
[0061] (1) Sodium nitrate, vanadium acetylacetonate, manganese acetate, phosphoric acid, and boric acid in a molar ratio of 4:1.0:1.0:1.5:1.5 are added to an ethanol solution containing citric acid, and the molar ratio of citric acid to transition metal salt is 1:1; then the mixed solution is placed on a constant temperature heating table at 60° C. and magnetically stirred at a speed of 300 rpm. After stirring for 6 hours, the solvent is completely evaporated to obtain a precursor;
[0062] (2) The precursor is placed in a tubular furnace in an argon atmosphere and sintered at 800° C. for 4 hours to obtain a high entropy polyanion positive electrode material.
[0063] Comparative Example 5
[0064] (1) Sodium nitrate, vanadium acetylacetonate, aluminum acetate, zinc acetate, phosphoric acid, ammonium sulfate, and boric acid in a molar ratio of 2.6:1.0:0.6:0.4:1.5:0.8:0.7 are added to an ethanol solution containing citric acid, and the molar ratio of citric acid to transition metal salt is 1:1; then the mixed solution is placed on a constant temperature heating table at 60°C and magnetically stirred at a speed of 300 rpm. After stirring for 6 hours, the solvent evaporates completely to obtain a precursor;
[0065] (2) The precursor is placed in a tubular furnace in an argon atmosphere and sintered at 800° C. for 4 hours to obtain a high entropy polyanion positive electrode material.
[0066] Comparative Example 6
[0067] (1) Sodium nitrate, vanadium acetylacetonate, manganese acetate, tetrabutyl titanate, phosphoric acid, ammonium sulfate, and boric acid in a molar ratio of 3:0.4:1.2:0.4:1.5:0.8:0.7 are added to an ethanol solution containing citric acid, and the molar ratio of citric acid to transition metal salt is 1:1; the mixed solution is then placed on a constant temperature heating table at 60°C and magnetically stirred at a speed of 300 rpm. After stirring for 6 hours, the solvent evaporates completely to obtain a precursor;
[0068] (2) The precursor is placed in a tubular furnace in an argon atmosphere and sintered at 800° C. for 4 hours to obtain a high entropy polyanion positive electrode material.
[0069] Comparative Example 7
[0070] (1) Sodium nitrate, vanadium acetylacetonate, manganese acetate, tetrabutyl titanate, phosphoric acid, ammonium sulfate, and boric acid in a molar ratio of 3.1:1.0:0.6:0.4:1.5:0.1:1.4 are added to an ethanol solution containing citric acid, and the molar ratio of citric acid to transition metal salt is 1:1. The mixed solution is then placed on a constant temperature heating table at 60°C and magnetically stirred at a speed of 300 rpm. After stirring for 6 hours, the solvent evaporates completely to obtain a precursor;
[0071] (2) The precursor is placed in a tubular furnace in an argon atmosphere and sintered at 800° C. for 4 hours to obtain a high entropy polyanion positive electrode material.
[0072] The sodium ion button cells assembled in the examples and comparative examples were first prepared by mixing the prepared high entropy polyanion material as the positive electrode active material with conductive carbon black and conductive binder PTFE in an agate mortar at a mass ratio of 8:1:1 and grinding for 30 minutes. After grinding, the material was rolled into a 0.8*0.8 square electrode sheet with an active material surface density of 8-10 mg / cm 2. The rolled electrode piece is vacuum dried at 120°C for 6 hours. After cooling to below 30°C, it is placed in a glove box for standby use. Battery assembly process: Use a CR2032 electrode shell to assemble button cells in the order of placing the negative electrode shell, metallic sodium, diaphragm, positive electrode piece, gasket, spring sheet, and positive electrode shell. The diaphragm uses a glass fiber diaphragm, and the electrolyte uses a 1.0M sodium perchlorate (NaClO4) solution of propylene carbonate (PC) containing 2% fluoroethylene carbonate (FEC). The amount of electrolyte added is 120μL. After assembly, it is packaged with a button battery press. After standing for 6 hours, the assembled battery is tested for charge and discharge at room temperature (25°C) using the Wuhan Blue Electric test system. The button battery assembled in Example 1 is tested at 0.2C (1C = 110mAh g -1 ) under the charge and discharge curves as shown in Figure 4 The test results of the embodiments and comparative examples are shown in Table 1:
[0073] Table 1
[0074]
[0075] As can be seen from Table 1, the 0.2C discharge capacity of the battery prepared by using the positive electrode material of the present invention in Examples 1-3 can reach 110 mAh g -1 Above, the 2C discharge capacity can reach 105mAh g -1 , the capacity retention rate can reach more than 97% after 100 cycles at 2C, and the discharge medium voltage can reach more than 3.455V. Through the coordinated high entropy regulation of anions and cations, the 0.2C discharge specific capacity can reach 117mAh g -1 , 2C discharge capacity can reach 111mAh g -1 , the capacity retention rate can reach 98% after 100 cycles at 2C, and the discharge medium voltage can reach 3.495V.
[0076] By comparing Example 1 with Comparative Example 1, it can be seen that the present invention introduces a high entropy anion-cation synergistic doping strategy, and the material charge and discharge platform is effectively improved. This shows that the anion-cation synergistic doping of the present invention can effectively reduce the cost of raw materials, adjust local chemical bonds and electron distribution, and achieve precise lattice control. After doping, the discharge capacity of the material is significantly improved, and the cycle retention rate is greatly improved.
[0077] From the comparison between Example 1 and Comparative Example 2, it can be seen that the coordinated design of cations has a significant improvement effect on the working voltage and discharge capacity of the material. Only when the transition metal sources A, B, and C exist at the same time can better electrochemical performance be obtained.
[0078] From the comparison between Example 1 and Comparative Example 3, it can be seen that the synergistic effect of anions has a significant improvement effect on the cycle stability and discharge capacity of the material. Only when the polyanion sources X, Y, and Z exist at the same time can a better sodium storage performance be obtained.
[0079] From the comparison between Example 1 and Comparative Example 4, it can be seen that the coordinated component design of anions and cations has a directional effect on improving the overall electrochemical properties of the material. Only when the transition metal sources A, B, C and the polyanion sources X, Y, Z exist at the same time can the structural stability, working voltage and conductive properties of the material be coordinated and regulated.
[0080] From the comparison between Example 1 and Comparative Example 5, it can be seen that only by selecting the selected transition metal source can the effect of directional regulation of the structure to improve the sodium storage performance be achieved. Even if the transition metal source outside the limited range can obtain a high entropy structure, it has no functional characteristics and cannot obtain good electrochemical performance.
[0081] It can be seen from the comparison between Example 1 and Comparative Example 6 that only when the ratio of transition metal sources is appropriate can the effect of directional regulation of crystal structure stability and improvement of sodium storage performance be achieved. High entropy components that are not within the specified range cannot achieve the ideal regulation effect and it is difficult to obtain good cycle performance.
[0082] By comparing Example 1 and Comparative Example 7, it can be seen that only when the proportion of polyanion source is appropriate can the effect of directional voltage regulation and improvement of sodium storage performance be achieved. High entropy components that are not within the specified range cannot achieve the ideal operating voltage and it is difficult to obtain a higher energy density. The high entropy design with a limited proportion of transition metal source and polyanion source can not only fully reflect the electrochemical properties of each element / group, improve voltage and capacity, but also improve the disorder of the overall structure, alleviate the phase transition of the material during the cycle, and thus improve the cycle life of the material.
[0083] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A high entropy polyanion positive electrode material modified by anion and cation functionalization doping, characterized in that: The positive electrode material comprises a positive electrode core and a carbon coating layer, and the chemical formula of the positive electrode core is Na δ A α B β C γ X σ Y m Z n , where A is V 3+ and / or Fe 2+ , B is Cu 2+ , Mn 2+ and Cr 3+ One or more of the following, C is Ni 2+ and / or Ti 4+ , X is PO4 3- and / or P2O7 4- , Y is SO4 2- 、N 3- and F - More than one of the following, Z is BO3 3- 、SiO4 4- , S 2- and Cl - At least one of the following, 2≤δ≤3.5, 0.8≤α≤1.2, 0.3≤β≤0.6, 0.4≤γ≤0.6, 2.2≤σ≤2.6, 0.2≤m≤0.5, 0.2≤n≤0.4; the particle size of the high entropy polyanion positive electrode material is 10μm~40μm, and the thickness of the carbon coating layer is 5nm~10nm.
2. The high entropy polyanion positive electrode material modified by anion and cation functionalization doping as claimed in claim 1, characterized in that: The chemical formula of the positive electrode core is Na 2.6 VFe 0.2 Mn 0.3 Ti 0.5 (PO4) 2.2 (SO4) 0.4 (BO3) 0.4 、Na3VMn 0.5 Ti 0.5 (PO4) 2.4 (SO4) 0.3 (BO3) 0.3 、Na 3.1 V 0.8 Fe 0.4 Mn 0.4 Ti 0.4 (PO4) 2.4 (SO4) 0.3 (BO3) 0.3 、Na 2.4 V 0.6 Ti 0.4 (PO4) 2.6 (SO4) 0.2 (BO3) 0.2 、Na 3.5 Fe 0.9 Mn 0.6 Ti 0.5 (PO4) 2.2 (SO4) 0.5 (BO3) 0.3 Or Na 3.3 VFe 0.2 Cu 0.3 Ti 0.5 (PO4) 2.2 (SO4) 0.4 (BO3) 0.4 .
3. A method for preparing the high entropy polyanion positive electrode material modified by anion and cation functionalization doping as claimed in claim 1 or 2, characterized in that: The method steps include: (1) adding a sodium source, a transition metal A source, a transition metal B source, a transition metal C source, a polyanion X source, a polyanion Y source, a polyanion Z source and a carbon source into a volatile solvent, heating and stirring until the solvent evaporates to dryness, thereby obtaining a precursor; (2) sintering the precursor in a protective gas atmosphere to obtain a high-entropy polyanion positive electrode material modified by anion and cation functionalization doping; Wherein, in step (1), the molar ratio of the sodium source to the total amount of the transition metal source is 0.6-2.4:1, the molar ratio of the sodium source to the total amount of the polyanion source is 0.4-1.6:1, and the molar ratio of the carbon source to the total amount of the transition metal source is 1-6:1; In step (2), the sintering temperature is 300°C to 800°C, and the sintering time is 4h to 20h.
4. The method for preparing a high entropy polyanion positive electrode material modified by anion and cation functionalization doping as claimed in claim 3, characterized in that: In step (1), the molar ratio of the sodium source to the total amount of the transition metal source is 1-2:1, the molar ratio of the sodium source to the total amount of the polyanion source is 0.8-1.2:1, and the molar ratio of the carbon source to the total amount of the transition metal source is 3-6:
1.
5. The method for preparing a high entropy polyanion positive electrode material modified by anion and cation functionalization doping as claimed in claim 3, characterized in that: In step (1), the sodium source includes one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium formate, sodium acetate and sodium nitrate; In step (1), in the source of transition metal A, the vanadium source is one or more of vanadium trichloride, vanadium tribromide, vanadium trioxide, vanadium acetylacetonate, vanadium oxychloride, vanadium oxysulfate, vanadium oxyoxalate, vanadium dioxide, vanadium acetylacetonate, vanadium oxychloride, sodium vanadate, sodium metavanadate, ammonium metavanadate, vanadium pentoxide and metallurgical vanadium slag; the iron source is one or more of ferrous fluoride, ferrous chloride, ferrous bromide, ferrous nitrate, ferrous sulfate, ferrous carbonate, ferrous oxalate, ferrous acetate, ferrous hydroxide, ferrous oxide, ferrous sulfide, ferrous acetylacetonate, ferrous trifluoride, ferric chloride, ferric bromide, ferric nitrate, ferric sulfate, ferric carbonate, ferrous oxalate, ferric acetate, ferric hydroxide, ferrous trioxide, ferrous tetroxide and ferrous acetylacetonate; In the transition metal B source, the copper source is one or more of copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide and copper acetylacetonate; the manganese source is one or more of manganous fluoride, manganous chloride, manganous bromide, manganous nitrate, manganous sulfate, manganous carbonate, manganous oxalate, manganous acetate, manganous hydroxide, manganous oxide, manganous sulfide, manganous acetylacetonate, manganous trifluoride, manganous trichloride, manganous tribromide, manganous nitrate, manganous sulfate, manganous carbonate, manganous oxalate, manganous acetate, manganous hydroxide, manganous trioxide, manganous dioxide and manganous acetylacetonate; the chromium source includes one or more of chromium trichloride, chromium tribromide, chromium nitrate, chromium sulfate, chromium oxalate, chromium formate, chromium acetate, chromium chromate, chromium lactate, basic chromium sulfate, chromium perchlorate, chromium trioxide, chromium hydroxide, chromium acetylacetonate, sodium chromate and sodium dichromate; In the transition metal C source, the nickel source is one or more of nickelous fluoride, nickelous chloride, nickelous bromide, nickelous nitrate, nickelous sulfate, nickelous carbonate, nickelous oxalate, nickelous acetate, nickelous hydroxide, nickelous oxide, nickelous sulfide and nickelous acetylacetonate; the titanium source is one or more of titanium chloride, titanium bromide, titanium sulfate, titanium nitrate, titanium oxalate, titanium formate, titanium acetate, titanium dioxide, titanium acetylacetonate and tetrabutyl titanate; When the transition metal exhibits a high valence, a reducing agent is also added; In step (1), the polyanion X source is PO4 3- 、P2O7 4- The corresponding acid and / or salt; the polyanion Y source includes SO4 2- 、N 3- 、F - The corresponding acid and / or salt; the polyanion Z source is BO3 3- 、SiO4 4- , S 2- , Cl - SO4 2- 、N 3- 、F - corresponding acids and / or salts; In step (1), the carbon source includes one or more of citric acid, sodium citrate, sodium oleate, oleic acid, polyvinyl pyrrolidone, glucose, sucrose, starch, dopamine hydrochloride, graphene, Ketjen black and carbon nanotubes.
6. The method for preparing a high entropy polyanion positive electrode material modified by anion and cation functionalization doping as claimed in claim 5, characterized in that: The reducing agent includes one or more of ascorbic acid, oxalic acid, citric acid, charcoal and hydroxylamine hydrochloride.
7. The method for preparing a high entropy polyanion positive electrode material modified by anion and cation functionalization doping as claimed in claim 5, characterized in that: In step (1), the solvent is one or more of water, ethanol, acetone and ethyl acetate; the heating and stirring temperature is 60°C to 200°C, the stirring speed is 300rpm to 1000rpm, and the time is 1h to 6h.
8. The method for preparing a high entropy polyanion positive electrode material modified by anion and cation functionalization doping as claimed in claim 5, characterized in that: In step (2), the sintering temperature is 400° C. to 600° C., and the sintering time is 6 h to 12 h; the protective gas is nitrogen or an inert gas.
9. A sodium ion battery, characterized in that: The positive electrode material of the battery adopts a high entropy polyanion positive electrode material modified by anion and cation functionalization doping as described in claim 1 or 2.
Citation Information
Patent Citations
Modified titanium-manganese-sodium phosphate positive electrode material as well as preparation method and application thereof
CN113422043A
Manganese-based polyanion positive electrode material, preparation method thereof and sodium ion battery
CN114142026A
Polyanionic high-voltage sodium ion battery positive electrode material and preparation method thereof
CN114361421A
Phosphate positive electrode material and preparation method and application thereof
CN112421040A
Double-site doped modified sodium vanadium phosphate positive electrode material as well as preparation method and application thereof
CN114156453A
